The role of biofilm formation in reverse osmosis membrane system performance and possible antifouling strategies - Chen, Xi (2015)
In this study, confocal microscope observation coupled with the fluorescence staining was employed to monitor biofouling of Reverse Osmosis (RO) membranes using Pseudomonas aeruginosa and Pseudomonas fluorescence as model fouling organisms. A range of parameters, including the presence of feed channel spacers, nutrient level, flux and cross-flow velocity were compared to determine their roles in biofouling. In addition, novel biofouling controls (UV pretreatment and NO addition) were tested to determine their efficacy as biofilm control agents. It was found that biofilm formation resulted in a slow rise in TMP and followed by a sharp increase, called the ‘TMP jump’. The initial slow increase in TMP was most likely due to the formation of a biofilm on the membrane surface, which then accelerated the biofouling rate through cake-enhanced polarization of nutrients. It was observed that nutrient limitation slowed biofilm accumulation and delayed the increase in TMP. It was evident that the presence of the spacer improved the performance of the RO system. In the presence of the spacer, biofilm development was slower and the TMP showed a much slower rise. When a spacer was introduced into the membrane module, the biofilm primarily occurred on the membrane, not on the spacer. While the inclusion of spacers delayed fouling, a faster TMP rise was observed under conditions of higher flux and lower cross-flow velocity. Two approaches were examined to control biofilm development and hence, to improve the performance of the RO system, UV pretreatment to kill the bacteria in the feed and induction of biofilm dispersal using Nitric Oxide (NO). UV pretreatment effectively inactivated bacteria in the feed. While UV treatment delayed biofilm formation and fouling, it did not prevent biofilm formation. Preliminary data showed that the NO donor, Sodium NitroPrusside (SNP) could disperse biofilms formed on RO membranes. The results presented here suggest that improving hydrodynamics (e.g. reducing the flux, increasing cross-flow) in membrane modules in combination with limiting nutrient concentrations in the feed as well as rationally-designed feed spacers could be used to control biofouling and improve system performance.